Thirty second chair stand test: Test–retest reliability, agreement and minimum detectable change in people with early‐stage knee osteoarthritis. (19th May 2022) - Gill, Stephen; Hely, Rachael; Page, Richard S.; Hely, Andrew; Harrison, Benjamin; Landers, Steve
Abstract: Background and Purpose: To determine intra‐session test‐retest reliability, agreement and minimum detectable change (MDC) of the 30 CST across three tests in people with knee osteoarthritis (OA). Methods: A test–retest reliability study was performed with 93 people with mild radiological knee OA. Participants were asked to complete three attempts of the 30 CST 1–2 min apart according to a standardised protocol. Participants completed three attempts on two occasions: baseline and 6 months later. Change between tests within each session was assessed with ANOVA's and post‐hoc t ‐tests. Reliability was assessed with intra‐class correlation coefficients (ICC[2, 1] ). Measurement error was expressed as MDC for an individual (MDCind ) and a group (MDCgroup ). Floor effects were considered present if more than 15% of participants scored zero for a test. Results: Scores increased by 0.5 and 0.8 stands between the first and second test ( p < 0.05) at the baseline and 6‐month assessments respectively, and then stabilised between the second the third tests at the baseline assessment ( p > 0.05) or decreased (0.3 stands) at the 6‐month assessment ( p < 0.05). Scores demonstrated excellent reliability (ICCs >0.9). MDCind was approximately 2.5 stands and MDCgroup was 0.3–0.4 stands. No floor effects were apparent. Discussion: The 30CST demonstrated a practice effect between the first and second tests, which was no longer apparent by the third test. Despite this, scores demonstrated excellent intra‐session reliability. MDC estimates provide clinicians and researchers with the smallest change that can be detected by the instrument beyond measurement error for individuals and groups in community‐dwelling adults with knee OA.